Effect of Interpersonal Communication and the Work Environment on Employee Performance PT.Systran Electronics Card Zone Batam - Fitri, Kurniawaty; ', Muapia; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Human resources as one of the internal factors that play an important role in the success or failure of anorganization's goals. PT. Systran Electronics Company Zone Card Batam is a company engaged in the manufacture of electrical passport in the hope this effort can be developed in the future and is able to utilize the development of increasingly sophisticated technology. To that end, the Company PT.Systran Electronics Card Zone should pay attention to the performance of its employees, especially in terms of interpersonal communication and a good working environment and coordinate all elements of the activities carried out by their employees to be motivated to improve their performance. The purpose of this study was to analyze the influence of interpersonal communication and work environment on employee performance. The data used is primary data in the form of questionnaires obtained from company employees PT.Systran Electronics Card Zone as a respondent. The population in this study were all employees of as many as 42 people. Sampling technique used is the census sample, in which all members of the population sampled. To analyze the effect of interpersonal communication and work environment on employee performance used multiple linear regression statistical analysis. Results showed that interpersonal communication and work environment either simultaneously or partial effect on employee performance. The most dominant variable in affecting the performance of employees is interpersonal communication, followed by a variable work environment. From the conclusions obtained from this study, the researchers gave some suggestions from the results of this study are expected to pay more attention to the company PT. SEZCard side of interpersonal communication and the working environment of employees in order to obtain the maximum performance of employees, focusing attention in terms of equality of employees, and establish individual good of subordinates to superiors and superiors to subordinates in order to realize the vision and mission of the company in the future.Keywords : Employee Performance, Interpersonal Communication, Work Environment.